Tensile Plasticity of Miniature Specimens for a Low Alloy Steel Investigated by Digital Image Correlation Technique. Issue 7 (16th April 2021) - Yang, Wen-Ke; Wang, Li-Yi; Song, Zhu-Man; Luo, Xue-Mei; Zhang, Guang-Ping
Abstract : Miniature specimens are widely being used to determine tensile properties of various size‐limited new materials, especially quickly evaluate or monitor changes in mechanical properties of in‐service reactor components to ensure their continuous operation with large safe margins. Although tensile properties of the miniature specimens are investigated extensively, the basic mechanism on such size effects, especially tensile plasticity, is not understood well. Here, tensile properties of A588 low alloy steel specimens with different gauge lengths and thicknesses are systematically investigated in situ using the digital image correlation technique. The findings reveal that the increase in the post‐necking elongation with decreasing the specimen gauge length and the decrease with decreasing the specimen thickness are due to the scale‐dependent strain‐rate sensitivity, whereas the constant uniform elongation is attributed to the stable strain hardening exponent. An empirical formula on the relationship between the total elongation and the strain‐rate sensitivity is proposed to describe the basic mechanism behind the specimen size‐dependent elongation. Abstract : A digital image correlation technique and GOM software are used in combination to explore the specimen size effect on tensile properties of A588 low alloy steel. The post‐necking elongation is affected by specimen size, which results from the scale‐dependent strain‐rate sensitivity exponent. An empirical formula is obtained when considering the strain‐rate sensitivity exponent and total elongation together.